Pluronic® F-127 and Pluronic Lecithin Organogel (PLO): Main Features and their Applications in Topical and Transdermal Administration of Drugs - Hugo Almeida; Maria Helena Amaral; Paulo Lobão; José Manuel Sousa Lobo (Frontiers Media S.A., 2012)
Topical drug treatment aims at providing high concentrations of drugs at the site of application so as to avoid adverse systemic effects associated with oral administration. Smart polymers, or stimuli-responsive polymers, are able to respond to a stimulus by showing physical or chemical changes in their behaviour as, for example, the delivery of the drug carried by them. The thermo-responsive nature of Pluronic® F-127 (Basf, Ludwigshafen, Germany) makes it an excellent candidate for the delivery of drugs at various application sites. In recent years, PF-127, and later, Pluronic lecithin organogels (PLO), have attracted particular interest in the design of dermal and transdermal delivery systems with a view to promoting, improving or retarding drug permeation through the skin, bearing in mind that for topical delivery systems, accumulation in the skin with minimal permeation is desired, while for systemic delivery, the opposite behaviour is preferred. In this review, we discuss the properties and characteristics of PF-127 and Pluronic lecithin organogels (PLO), and present many examples and advantages of the application of these polymeric systems in topical and transdermal administration of drugs. This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.